GAMBARAN KONSUMSI BUAH PINANG, KEJADIAN KECACINGAN DAN STATUS GIZI SISWA DI SD 175750 DESA PARDAMEAN NAINGGOLAN KECAMATAN PAHAE JAE KABUPATEN TAPANULI UTARA TAHUN 2013 - Lamria Sitompul; Albiner Siagian; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Areca catechu is a plant that belongs to coconut family. The people of Toba Batak use the fruit as one meal for friends or quests, as the substitution of the cigarette for men. For children, the fruit of areca catechu is used as the substitution for candy. This research is intended to know the description of the consumption of the fruit of areca catechu, the occurrence of suffering worms, and nutritional status of Elementary School 175750 in Pardamean Nainggolan village, Pahae Jae district, North Tapanuli regency in 2013. This was descriptive research with cross-sectional design. The sample of research was 58 students consisting of class 4 and class 6 who consumed the fruit of areca catechu and who did not consume the fruit of areca catechu. The results of research showed 91.4% of the students in Pardamean Nainggolan village consumed the fruit of areca catechu and mostly of them consumed with the frequency once or twice in a day and quantity of consumption mostly 1- 3 fruit in a day, who mostly consumed during the day. From the result of helminthiasis checking, 94.8% the students of Elementary School classified negative and 5.2% classified positive. Mostly of student consumed energy and protein in worse deficit level, that was each for 86.2% and 53.4% respectively. The description on the nutritional status of Elementary School based on H/A as normal 67,2%, short 31% and very short 1,7% and based on BMI/A 84.5% as normal 84,5% and thin 6,9%. It is suggested for the health center to give guidance and counseling about the consumption of the fruit of areca catechu. In addition, there should be the control for suffering worms and socialization about General Guide of Balanced Nutrient. Hemoglobin test should be conducted for the students of Elementary School 175750 Pardamaen Nainggolan village. Key words : areca catechu fruit consumption, suffering worms, nutritional status, the students of elementary school